2010
DOI: 10.1089/gtmb.2009.0192
|View full text |Cite
|
Sign up to set email alerts
|

PTPN11 and KRAS Gene Analysis in Patients with Noonan and Noonan-Like Syndromes

Abstract: Noonan and Noonan-like syndromes are disorders of dysregulation of the rat sarcoma viral oncogene homolog (RAS)-mitogen-activated protein kinase signaling pathway. In Noonan syndrome (NS), four genes of this pathway (PTPN11, SOS1, RAF1, and KRAS) are responsible for roughly 70% of the cases. We analyzed PTPN11 and KRAS genes by bidirectional sequencing in 95 probands with NS and 29 with Noonan-like syndromes, including previously reported patients already screened for PTPN11 gene mutations. In the new patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 48 publications
3
27
0
Order By: Relevance
“…Two previous studies (14,15), including one from our group, showed the presence of one known pathogenic mutation and another gene alteration that probably functions as a modifier. We described a NS patient presenting the pathogenic p.N308D mutation in the PTPN11 gene and also the p.N85S mutation in the KRAS gene (14). The patient presented typical features of NS and learning disabilities, which is not common, but far from an exception, in individuals with the p.N308D mutation in the PTPN11 gene.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Two previous studies (14,15), including one from our group, showed the presence of one known pathogenic mutation and another gene alteration that probably functions as a modifier. We described a NS patient presenting the pathogenic p.N308D mutation in the PTPN11 gene and also the p.N85S mutation in the KRAS gene (14). The patient presented typical features of NS and learning disabilities, which is not common, but far from an exception, in individuals with the p.N308D mutation in the PTPN11 gene.…”
Section: Discussionmentioning
confidence: 69%
“…In our group we identified five other NS patients with p.N308S mutation in the PTPN11 gene and one patient with p.R552G mutation in the SOS1 gene (14,27). The phenotype of these patients did not significantly differ from the patient harboring both mutations (Table 3).…”
Section: Phenotype Analysismentioning
confidence: 79%
See 2 more Smart Citations
“…As discussed above, both of these variants cause increased ERK activation in transfected heterologous cells. Co-occurring mutations in NS-causing genes have been reported in a few patients with NS (38)(39)(40). Additive or modifying effects were observed in a NS patient carrying SHOC2 and PTPN11 mutations and in another individual harboring PTPN11 and KRAS mutations.…”
Section: Significancementioning
confidence: 95%